Scolopendra Pharmacopuncture Combined with Electroacupuncture for the Treatment of Ganglion Cysts: A Retrospective Study - Seon Choe; Ui Min Jerng; Jeong Hwan Park; Sungha Kim; Sungchul Kim; Jinbok Lee; Jun-Hwan Lee; Minseop Shin (Korean Pharmacopuncture Institute, 2020)
Objectives: Ganglion cysts require a sustainable treatment that suppresses their frequent recurrence. This study aimed to explore the clinical effects of Scolopendra pharmacopuncture (SP) and electroacupuncture on ganglion cysts.Methods: We retrospectively reviewed the patient records and follow-up reports for 20 patients with wrist ganglion cysts who received SP and electroacupuncture from April 2016 to March 2017. The cyst diameter, recurrence, visual analog scale (VAS) scores for pain, the Korean version of the disabilities of arm, shoulder, and hand (K-DASH) score, and the Korean version of the patientrated wrist evaluation (K-PRWE) score before and after treatment were noted.Results: After treatment, the cyst diameter decreased significantly from 13.61 ± 6.41 mm to 5.15 ± 6.18 mm (p < 0.001), and VAS score for pain decreased from 1.31 ± 1.77 to 0.41 ± 0.33 (p = 0.021). Further, the K-DASH score decreased significantly from 8.97 ± 12.66 to 2.21 ± 7.39 (p = 0.016), and score for the function subscale of K-PRWE decreased from 11.37 ± 4.48 to 9.1 ± 3.67 (p = 0.046). No recurrences were reported from the followed-up patients. Any complication related to SP or electroacupuncture was not observed, except mild rash, itching, and swelling at the injection site in four patients.Conclusion: Combination of SP and electroacupuncture may be effective in treating ganglion cysts; further prospective studies with large population are needed to clarify the effect of SP and electroacupuncture.